PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS-GAMES-TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK BUNYI DI KELAS VIII SEMESTER II SMP NEGERI 2 LUBUK PAKAM T.P. 2013/2014 - Karya Sinulingga; Ilyas Ilyas (UNIVERSITAS NEGERI MEDAN, 2015)
This research aimed to determine the effect of Teams-Games-Tournament on physics learning outcomes of students in the subject matter Sounds for VIII class SMP Negeri 2 Lubuk Pakam T.P. 2013/2014. The study was quasi-experimental with the entire populations of eighth grade students of SMP Negeri 2 Lubuk Pakam consisting of 10 classes. Sample were taken 2 classes are determined by cluster random sampling technique. Both of class given different treatment, The class VIII-8 using Teams-Games-Tournament and the class VIII-10 using conventional learning. The instrument used in this research is test of learning outcomes in the form of multiples with 5 options in 20 questions that have been declared valid and reliable by the experts. The results showed that the Teams Games Tournament can improve student learning outcomes and student learning activity. For student learning outcomes, the results of testing hypothesis using deffrent test, that are differences of student learning outcomes significantly due to the effect of Teams Games Tournament model in the subject matter Sounds second semester in VIII class SMP Negeri 2 Lubuk Pakam T.P. 2013/2014. Keywords : Cooperative Learning Type Teams-Games-Tournament, Sounds, Student Learning Outcomes